MUH. SYARIEF SUKANDI’S HARIRING WANGSITING GUSTI NU MAHA SUCI: POETIC TRANSLATION OF THE QUR’ĀN AND THE REFORMIST MUSLIM AMBIVALENCE - Jajang A Rohmana (Indonesian Journal of Islamic Literature and Muslim Society, 2021)
This study focuses on the tradition of Sundanese literary among the reformist Muslims. My object of study is a Sundanese book of poetic translation of the Qur’ān in the form of metrical verse or dangding entitle Hariring Wangsiting Gusti Nu Maha Suci (A Hymn of God Revelation the Most Holy) using translation approach and critical discourse analysis. The book is written by Muh. Syarief Sukandi (1931-1997). He was known as a member of Indonesian army, ‘ulamā’ and activist of reformist Islamic organization, Islamic Union (Persatuan Islam or Persis). Sukandi’s Hariring was published by Bina Insan Asy-Syarief Foundation in 2010. It contains 23 translations of the Qur’anic short surahs amount to 63 stanzas. He uses many types of metrum (pupuh). The study confirms that Sukandi’s Hariring tends to be a translation of exegesis (al-tarjamah al-tafsīriyyah) that was limited by the metrum rules. However, Sukandi’s Hariring is not only shows the influence of Sundanese nature, but also his effort to strengthen Islamic ideology which closer to pre-Islamic culture. It can be seen in the use of some Sundanese words of pre-Islamic period. It is an ambivalence that may be contrary to the purification ideology of Persis, because considered to contaminate the purity of Islamic teachings. It is a work of another side of reformist Muslim which do not keep the distance from local culture.